Exploring the provision of bus service for historical sites in south of Xi'an city - Zhang, Fang (2013)
Life today moves faster than ever before. As well as continued growth in traffic demand, the city traffic facing the growing challenges With the continuous expansion of the scale of Van City, the transportation infrastructure presents a serious shortage of the worsening traffic is no longer suitable the socio-economic development of Van and residents' needs. The suitable ways to solve the problem for Xi'an city, is improving the bus system, which is widely used in developing country. Thus this project it will determine the suitable bus route for the south part of Xi'an, and analysis of traffic flow for bus passenger demand based on consideration of users' time, cost and the flow of the pedestrian at the steps. The project can save the increase in travel time and helps lessen air pollution. This study can also can be applied for another similarly cities in China.